Estimating overpressures in pole-type distribution transformers. II. Prediction tools. - Dastous, J.-B (IEEE Transactions on power delivery)
Low-impedance faults are difficult to contain from the point of view of cover retention and tank rupture in pole-type distribution transformers. When evaluating a transformer's containment capabilities, one needs to consider two aspects: the overpressure caused by an arc of given parameters and the pressure withstand of the tank. This paper presents two methods to calculate overpressures as a function of the arc and all of the relevant geometrical parameters: tank diameter, air-space height, and the depth of the arc below the oil. Both methods have been validated with experiments. Results of tests to determine the pressure withstand of typical tanks are presented. It was found that an average value of the overpressure withstand capability is approximately 100 kPa. For a given tank geometry and fault parameters, a current-limiting fuse would be required if the methods proposed here predict an overpressure of more than 100 kPa.